Sweat loss and fluid intake of female varsity ice hockey players during on-ice practices and games - Bigg, J. L.; Gamble, A. S.; Vermeulen, T. F.; Bigg, L. M.; Spriet, L. L. (The Journal of Strength and Conditioning Research, 2020)
Sweat losses of ~1.5-2% body mass (BM) during exercise impairs athletic performance in stop and go sports such as ice hockey. The study examined the pre-exercise hydration status, sweat loss, fluid and carbohydrate (CHO) intake, and sodium balance of female hockey players. Twenty-four female varsity hockey players were tested during 2 practices and 4 games. Data analyses were performed using a level of significance of p = 0.05. Over 70% of players arrived at the practices and ~50% of players arrived at the game mildly dehydrated. Before the high- (P1) and low-intensity (P2) practices, players consumed an average of 0.19 ± 0.14 and 0.15 ± 0.13 L. Before the games, mean fluid intake was 0.39 ± 0.19 L. The sweat rate during P1 was significantly greater than P2 (p = 0.006), but there was no significant difference in total fluid intake between practices (p = 0.279). Consequently, the average BM loss for P1 was significantly greater than that for P2 (p = 0.016). Sweat loss during games was 1.01 ± 0.29 L and fluid intake was 0.70 ± 0.43 L, resulting in minimal BM losses (<1% BM for all players). CHO intake during games was 39.2 ± 22.8 g, with 19/20 players consuming CHO before or during the intermissions of the game. Sweat sodium losses were 0.64 ± 0.34 and 0.32 ± 0.18 g·h-1 for P1 and P2, and 0.83 ± 0.38 g during the game. In conclusion, female ice hockey players replaced the fluid they lost through sweat during practices and games and maintained adequate hydration. Players also consumed adequate CHO during games from the CHO containing food and drinks provided.